Peningkatkan Aktivitas Siswa Menggunakan Media Papan Catur tentang Materi Pewarisan Sifat Kelas IX SMPN 4 Kota Solok - Hurriyati Hurriyati (JURNAL EKSAKTA PENDIDIKAN (JEP), 2020)
Material inheritance is one of the materials in science subjects that students are less interested in. This can be seen from the low motivation of students in learning. In addition, in this material students are required to use a variety of terms that are new to them, using letter symbols to indicate characteristic or genes in order to be able to cross and be able to determine the choice of genotypes and phenotypes resulting from these crosses. The purpose of this study was to increase the activities of students who use chess boards on material inheritance. This research is a Classroom Action Research (CAR) which was conducted in two cycles. The subjects of this study were 30 students in class IXa. The results of this study indicate the use of chessboard media on class nature inheritance material in class IXa students at SMPN 4 Solok City can increase student activity. Thus this media can be used in learning to increase student activity on material inheritance.